1999
DOI: 10.1111/j.1365-2141.1999.01318.x
|View full text |Cite
|
Sign up to set email alerts
|

A metalloproteinase inhibitor prevents acute graft‐versus‐host disease while preserving the graft‐versus‐leukaemia effect of allogeneic bone marrow transplantation

Abstract: Summary.We examined the effect of a hydroxamic acidbased matrix metalloproteinase inhibitor (KB-R7785), which we previously demonstrated to have a potent ameliorating effect on acute graft-versus-host disease (GVHD), and on the graft-versus-leukaemia (GVL) effect of allogeneic bone marrow transplantation (BMT). KB-R7785 was administered to (C57BL/6 × BALB/c) F1 (CBF1) mice that had been inoculated with IgE-producing B53 hybridoma cells of BALB/c origin as a model tumour, along with or without transplantation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Because MMP inhibitor prevented lethal acute graft-versus-host disease in mice (19,20), we hypothesized that in addition to the cytokinemodulating effect of MMPs, they might also be lesionally expressed and contribute to destruction on the tissue level. In this work, we studied the expression of MMPs and TIMPs previously shown to be abundantly expressed in intestinal ulcers related to inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because MMP inhibitor prevented lethal acute graft-versus-host disease in mice (19,20), we hypothesized that in addition to the cytokinemodulating effect of MMPs, they might also be lesionally expressed and contribute to destruction on the tissue level. In this work, we studied the expression of MMPs and TIMPs previously shown to be abundantly expressed in intestinal ulcers related to inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…The synthetic MMP inhibitor (KB-R7785), with activity against MMPs-1, -3, and -9, prevents acute graft-versus-host disease but preserves graft-versusleukemia effect in mice undergoing allogeneic bone marrow transplantation (19,20). TNF-␣ and FasL, both released and activated by MMPs (3,21), are implicated in the pathogenesis of acute graftversus-host disease (22).…”
mentioning
confidence: 99%
“…Such a pattern may not be surprising as murine studies have shown that TNF␣ plays a predominant role in GVHD manifestations in the intestinal tract. 53 A retrospective analysis by Couriel et al in 21 patients with steroid-refractory acute GVHD showed a response rate of 60% with infliximab, with most responses being complete. 54 The rate of infection, in particular with fungal organisms, was high (hazard ratio, 13.6).…”
Section: Primary Therapy and Its Impactmentioning
confidence: 99%
“…Therefore, targeting the cleavage of membrane-bound TNF with a TACE inhibitor could be assessed as a new therapeutic strategy for attenuating gastrointestinal and hepatic GVHD without impacting GVT after allo-BMT. 18,19 …”
mentioning
confidence: 99%